2022
DOI: 10.1186/s12978-022-01494-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting reversible contraceptives use among adolescent girls and young women in high fertility countries in sub-Saharan Africa

Abstract: Background Given the instrumental role long-acting reversible contraceptives (LARCs) play in reducing unintended pregnancies, there is a need to understand the factors that predict their use among adolescent girls and young women in high fertility countries. Our study examined the prevalence and predictors of LARCs use among adolescent girls and young women in high fertility countries in sub-Saharan Africa. Materials and methods We pooled data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Regarding parity, women with three or more children were more likely to use both permanent and LARC methods. According to previous studies,4 62 63 using permanent and LARCs increases as children grow 64. One explanation could be that multiparous women frequently get FP information and counselling on contraceptive usage throughout their pregnancy counselling or that women who have previously achieved their desired fertility may take permanent contraceptives or LARCs until menopause 4 64.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding parity, women with three or more children were more likely to use both permanent and LARC methods. According to previous studies,4 62 63 using permanent and LARCs increases as children grow 64. One explanation could be that multiparous women frequently get FP information and counselling on contraceptive usage throughout their pregnancy counselling or that women who have previously achieved their desired fertility may take permanent contraceptives or LARCs until menopause 4 64.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors influence AGYW’s choices around pregnancy and contraceptive use, including individual opinions, social norms and living circumstances, misconceptions about contraceptives, and stigma among communities and healthcare providers [ 3 , 4 , 9 ]. Research has also shown that use of long-acting reversible contraceptives (LARCs) is particularly low among AGYW, while use of emergency contraception (EC) pills has been emerging as a more popular and accessible option among this group [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%